2023
DOI: 10.3390/children10071122
|View full text |Cite
|
Sign up to set email alerts
|

High CCL2 Levels Detected in CSF of Patients with Pediatric Pseudotumor Cerebri Syndrome

Abstract: Pseudotumor cerebri (PTC) is a disorder characterized by increased intracranial pressure in the absence of a structural lesion or other identifiable cause. Cytokines, which are involved in the regulation of immune responses and inflammation, have been implicated in the pathogenesis of PTC. In a prospective, cross-sectional study at three centers in Israel, we analyzed cerebrospinal fluid (CSF) samples from 60 children aged 0.5–18 years, including 43 children with a definitive diagnosis of PTC and a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study revealed a significant increase in chemokine ligand (C–C motif) 2 levels in the PTC group as compared to the control group ( p < 0.05). 119 Despite the variability in the results in different studies, the consistently observed abnormal expression of inflammatory mediators in most of them highlights a potential link between inflammation and IIH. 117 , 120 , 121 , 122 , 123 However, it should be noted that these investigations are constrained by factors such as limited sample sizes and heterogeneous populations, necessitating a cautious interpretation of these findings and highlighting the need for more extensive research.…”
Section: Hypothesis Of Pathological Mechanismmentioning
confidence: 98%
“…The study revealed a significant increase in chemokine ligand (C–C motif) 2 levels in the PTC group as compared to the control group ( p < 0.05). 119 Despite the variability in the results in different studies, the consistently observed abnormal expression of inflammatory mediators in most of them highlights a potential link between inflammation and IIH. 117 , 120 , 121 , 122 , 123 However, it should be noted that these investigations are constrained by factors such as limited sample sizes and heterogeneous populations, necessitating a cautious interpretation of these findings and highlighting the need for more extensive research.…”
Section: Hypothesis Of Pathological Mechanismmentioning
confidence: 98%